The influence of a community intervention on influenza vaccination knowledge and behavior among diabetic patients - Lili Tao; Ming Lu; Xiaoning Wang; Xiaoyan Han; Shuming Li; Haiyan Wang (BMC, 2019)
Abstract Background This study was conducted to evaluate the impact of a comprehensive community intervention on cognition and inoculation behaviors of diabetic patients immunized with influenza vaccine. Methods A total of 1538 diabetic patients aged 35 years and above for outpatient visits and follow-up treatments were selected from six community health service centers (three for the experimental group, and the other three for the control group) in Chaoyang District, Beijing. Comprehensive interventions applied to the experimental group include patient intervention and community climate interventions. We compared the total awareness of influenza vaccine knowledge and influenza vaccination rates between the two groups before and after the intervention. Results Before the intervention, the total awareness rate of influenza vaccine in the experimental group and the control group was similar (50.6 and 50.2%, respectively. P = 0.171). After the intervention, the awareness rate of influenza vaccine in the experimental group and the control group increased. The amplitude of the increase was similar (70.3 and 70.1%, respectively. P = 0.822,). Before the intervention, there was no significant difference in the influenza vaccination rate between the experimental group and the control group (29.0 and 26.8%, respectively. P = 0.334). After the intervention, the vaccination rate of the experimental group was higher than that of the control group. The difference was statistically significant (The vaccination rate 45.8 and 27.4% for the experimental group and the control group, respectively. P < 0.001). Conclusion Comprehensive community interventions had a positive effect on vaccination in diabetic patients. Trial registration ChiCTR1900025194, registered in Aug,16th, 2019. Retrospectively registered.